2015
DOI: 10.1021/acs.joc.5b00495
|View full text |Cite
|
Sign up to set email alerts
|

Densely Substituted l-Proline Esters as Catalysts for Asymmetric Michael Additions of Ketones to Nitroalkenes

Abstract: Homochiral methyl 4-aminopyrrolidine-2-carboxylates are readily obtained by means of asymmetric (3 + 2) cycloadditions between azomethine ylides and nitroalkenes, followed by catalytic hydrogenation of the intermediate 4-nitro cycloadducts. These 4-aminopyrrolidine-2-carboxylate esters belong to the L-series of natural amino acids and catalyze asymmetric Michael additions of ketones to nitroalkenes. However, the enantioselectivity observed with these novel unnatural organocatalysts is opposite to that obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…DFT calculations [26] on the most relevant transition structures involved in these Michael additions reproduced correctly the trends in enantioselectivity found in the experimental studies. The shape of the transition structures associated with the be- [24] havior of exo-47 and endo-47 showed that the enamine derived from the primary amino group must adopt axial and isoclinal dispositions in (R,1′S)-exo-TS6 and (S,1′R)-endo-TS6, respectively ( Figure 8).…”
Section: Densely Substituted Prolines As Organocatalystssupporting
confidence: 68%
See 3 more Smart Citations
“…DFT calculations [26] on the most relevant transition structures involved in these Michael additions reproduced correctly the trends in enantioselectivity found in the experimental studies. The shape of the transition structures associated with the be- [24] havior of exo-47 and endo-47 showed that the enamine derived from the primary amino group must adopt axial and isoclinal dispositions in (R,1′S)-exo-TS6 and (S,1′R)-endo-TS6, respectively ( Figure 8).…”
Section: Densely Substituted Prolines As Organocatalystssupporting
confidence: 68%
“…[24] Although 4-nitroprolines 28 were unable to catalyze Michael reaction between ketones and nitroalkenes, we found that the corresponding amino analogs 46, obtained by catalytic hydrogenation of their nitro precursors 28, catalyzed very efficiently this reaction. [26] As it is shown in Scheme 11, organocatalyst exo-46 generates Michael adducts (2R,1′S)-47 with good to excellent ee's. In contrast, diastereomer endo-46 gives rise to (2S,1′R)-47aa enantiomer, similar to that produced by L-Pro, with somewhat lower ee.…”
Section: Densely Substituted Prolines As Organocatalystsmentioning
confidence: 95%
See 2 more Smart Citations
“…[9] endo-6 Preferentially promoted the polymerization of D-lactide, whereas exo-6 preferentially polymerized L-lactide from a racemic mixture. [10] Michael-type addition of ketones to nitroalkenes [11] and a three component ketoneÀ carboxylic acidÀ nitroalkene cyclization [12] were successfully organocatalyzed by chiral exo-6 b (X = H), providing good to excellent diastereoselections and high enantiomeric ratios. A series of enantiopure tetrasubstituted nitroprolinate surrogates has been designed as scaffolds [ This publication is part of a Special Collection on "Silver Catalysis in Organic Synthesis".…”
Section: Introductionmentioning
confidence: 99%